2012
DOI: 10.1002/ajmg.a.35474
|View full text |Cite
|
Sign up to set email alerts
|

Simpson–Golabi–Behmel syndrome type 1 in a 27‐week macrosomic preterm newborn: The diagnostic value of rib malformations and index nail and finger hypoplasia

Abstract: The Simpson-Golabi-Behmel syndrome type 1 (SGBS1, OMIM #312870) is an X-linked overgrowth condition comprising abnormal facial appearance, supernumerary nipples, congenital heart defects, polydactyly, fingernail hypoplasia, increased risk of neonatal death and of neoplasia. It is caused by mutation/deletion of the GPC3 gene. We describe a macrosomic 27-week preterm newborn with SGBS1 who presents a novel GPC3 mutation and emphasize the phenotypic aspects which allow a correct diagnosis neonatally in particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Although we could not collect information for all clinical features in all cases and were thus unable to evaluate the precise frequency of rare associations, our study improves significantly the knowledge on SGBS. Our data may be compared with those of the 63 cases carrying a mutation in GPC3 for whom clinical details are available in the literature [Hughes‐Benzie et al, ; Lindsay et al, ; Veugelers et al, ; Okamoto et al, ; Li et al, ; Mariani et al, ; Day and Fryer, ; Rodríguez‐Criado et al, ; Young et al, ; Romanelli et al, ; Sakazume et al, ; Glamuzina et al, ; Gertsch et al, ; Gurrieri et al, ; Yano et al, ; Garavelli et al, ; Thomas et al, ; Li and McDonald, ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not collect information for all clinical features in all cases and were thus unable to evaluate the precise frequency of rare associations, our study improves significantly the knowledge on SGBS. Our data may be compared with those of the 63 cases carrying a mutation in GPC3 for whom clinical details are available in the literature [Hughes‐Benzie et al, ; Lindsay et al, ; Veugelers et al, ; Okamoto et al, ; Li et al, ; Mariani et al, ; Day and Fryer, ; Rodríguez‐Criado et al, ; Young et al, ; Romanelli et al, ; Sakazume et al, ; Glamuzina et al, ; Gertsch et al, ; Gurrieri et al, ; Yano et al, ; Garavelli et al, ; Thomas et al, ; Li and McDonald, ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we identified novel and early US findings that could improve the definition of the prenatal clinical picture of SGBS, and expanded the spectrum of fetal malformations thanks to the identification of anomalies appearing and detectable in the first trimester. We noted brain abnormalities including corpus callosum defects, absent septum pellucidum, cerebellar agenesis, and downward displacement of cerebellum in addition to ventriculomegaly, which had been the only brain structural alteration reported antenatally to date [Weichert et al, 2011;Garavelli et al, 2012;Cottereau et al, 2013]. Moreover, in the second pregnancy of family 1, we detected genital and intestinal defects and thyroglossal duct cysts, which have been described with undefined frequencies in SGBS individuals, but do not appear in the literature as prenatal findings.…”
Section: Discussionmentioning
confidence: 67%
“…Several authors have reported certain features on prenatal ultrasound that can facilitate SGB syndrome diagnosis before birth [Chen et al, 1993;Yamashita et al, 1995;Enns et al, 1998;Weichert et al, 2011;Garavelli et al, 2012;Cottereau et al, 2013;Kehrer et al, 2016;Magini et al, 2016;Mujezinović et al, 2016;Støve et al, 2017;Zimmermann and Stanek, 2017]. Table 1 summarizes the described prenatal findings from previously published cases and our cases.…”
Section: Discussionmentioning
confidence: 94%